Is Standardization the Future of Traditional Chinese Tuina (Massage) Therapy? - A Reflection on “Bibliometric Analysis of Research Trends on Tuina Manipulation for Neck Pain Treatment Over the Past 10 Years” [Letter] - Yao J; Shang Q; Cong D (Journal of Pain Research, 2024)
Junjie Yao,1 Qiangqiang Shang,2 Deyu Cong2 1College of Acupuncture and Tuina, Changchun University of Chinese Medicine, Changchun, Jilin, 130117, People’s Republic of China; 2Department of Tuina, The Affiliated Hospital to Changchun University of Chinese Medicine, Changchun, Jilin, 130021, People’s Republic of ChinaCorrespondence: Deyu Cong, Email congdeyu666@sina.com